Nucleic acid-free aptamer-CRISPR/Cas14 biosensor for prosthetic joint infection rapid detection - Zong-Jie Geng; Quan-Bo Ji; Yan-Jing Chen; Lin Hao; Jun-Song Wang; Ze-Yu Feng; Qing-Yuan Zheng; Guo-Qiang Zhang; Yan Wang (Sensors and Actuators Reports)
Rapid detection of live pathogens in prosthetic joint infections (PJI) remains a critical challenge in clinical practice. This study introduces a novel dual-aptamer CRISPR/Cas14 biosensor for rapid, equipment-minimized detection of live bacteria in clinical samples. Unlike existing aptamer-CRISPR platforms, our method integrates two aptamers: one biotinylated for magnetic bead-based bacterial enrichment, and the other to activate the CRISPR/Cas14 system. Cas14, chosen for its PAM-free ssDNA recognition and direct detection capability, triggers trans-cleavage of fluorophore-quencher-labeled ssDNA, generating fluorescence signals without nucleic acid extraction or amplification. This approach eliminates the need for centrifugation, significantly reducing equipment requirements and making it ideal for point-of-care testing. The method demonstrated high specificity, with detection limits of 10² CFU/mL for aptamer enrichment and 10 CFU/mL for CRISPR/Cas14 detection at room temperature (37 °C) . Clinical validation showed an 83.3 % positive concordance rate and 100 % negative concordance, with results obtainable within 15 min. By bypassing nucleic acid extraction and amplification, this dual-aptamer CRISPR/Cas14 biosensor offers a simple, rapid, and reliable solution for diagnosing PJI, with significant potential for clinical application.